Heart team consultations for patients with severe coronary artery disease or valvular heart disease in the era of the COVID-19 pandemic: a single-center experience - Jonik, Szymon; Boszko, Maria; Sztemberg, Elena; Łepecki, Dominik; Grodziński, Bartłomiej; Mikusek-Pham Van, Marcin; Marchel, Michał; Kochman, Janusz; Kuśmierczyk, Mariusz; Opolski, Grzegorz; Grabowski, Marcin; Mazurek, Tomasz (Frontiers in Cardiovascular Medicine, 2023)
Introduction The Heart Team (HT) as a group of experienced specialists is responsible for optimal decision-making for high-risk cardiac patients. The aim of this study was to investigate the impact of the COVID-19 pandemic on HT functioning. Methods In this retrospective, single-center study, we evaluated the cooperation of HT in terms of the frequency of meetings, the number of consulted patients, and the trends in choosing the optimal treatment strategies for complex individuals with severe coronary artery disease (CAD) or valvular heart disease (VHD) before and during the COVID-19 pandemic in Poland. Results From 2016 to May 2022, 301 HT meetings were held, and a total of 4,183 patients with severe CAD (2,060 patients) or severe VHD (2,123 patients) were presented. A significant decrease in the number of HT meetings and consulted patients (2019: 49 and 823 vs. 2020: 44 and 542 and 2021: 45 and 611, respectively, P < 0.001) as well as changes in treatment strategies—increase of conservative, reduction of invasive (2019: 16.7 and 51.9 patients/month vs. 2020: 20.4 and 24.8 patients/month and 2021:19.3 and 31.6 patients/month, respectively, P < 0.001)—were demonstrated with the spread of the COVID-19 pandemic. As the pandemic slowly receded, the observed changes began to return to the pre-pandemic trends. Conclusions The COVID-19 pandemic resulted in a decrease in the number of HT meetings and consulted patients and significant reduction of invasive procedures in favor of conservative management. Further studies should be aimed to evaluate the long-term implications of this phenomenon.